Fe3O4/graphene-oxide/chitosan hybrid aerogel based high performance supercapacitor: effect of aqueous electrolytes on storage capacity & cell stability. (February 2022) - Chadha, Neakanshika; Bhat, Md. Yasir; Hashmi, S.A.; Saini, Parveen
Highlights: Designing of RGOPF by decorating L-AA reduced graphene oxide (RGO) on polymeric foams (PFs). Utilisation of cost effective RGOPF as ESD safe packaging material for sensitive electronic devices. Low loading of RGO on PF provides surface resitivity of 10 7 Ω/sq for antistatic applications. The surface conductivity of RGO-PF increases as the concentration of RGO on PFs increases. The mechanism of interaction between RGO and PFs has been proposed. Abstract: In this work, Fe3 O4 /graphene-oxide/chitosan aerogel (GCFA) with 3-D interconnected structure (average pore size ∼8.4 nm) and moderate BET surface area (∼59 m 2 /g) is synthesized by hydrothermal route. Three different hybrid symmetric supercapacitor cells are fabricated using GCFA as active electrode material, using basic (6M KOH: cell-1), acidic (1M H2 SO4 : cell-2), & neutral (Na2 SO4 : cell-3) as electrolyte mediums. Subsequently, a comprehensive study is carried out to assess the effect of electrolyte on the porous architecture, charge storage capacity, rate capability and cyclic stability. Besides, cell-3 also shows good cyclic stability with low initial fading (∼15%), good capacity retention (∼84%) It has been observed that cell-3 displayed better performance (specific capacitance ∼160 F g −1, specific energy∼14.6 Wh kg −1 and specific power∼0.77 kW kg −1 ) than either of cell-2 (∼160 F g −1, ∼7.84 Wh kg −1 and ∼0.45 kW kg −1 ) or cell-1 (∼102 F g −1, ∼1.54 Wh kg −1 and ∼0.14 kW kg −1 ) and excellent coulombic efficiency (∼91%) even after 10, 000 charge-discharge cycles. This is attributed to the better pore accessibility, stability of residual surface functionalities under potential cycling, and least screening for intra-pore shuttling of counter-ions under neutral medium. Graphical abstract: Image, graphical abstract